2021
DOI: 10.1001/jamanetworkopen.2021.7112
|View full text |Cite|
|
Sign up to set email alerts
|

Trends in Drug Overdose Mortality in Ohio During the First 7 Months of the COVID-19 Pandemic

Abstract: This cross-sectional study uses data from the Ohio Department of Health to evaluate trends in drug overdose mortality in that state by type of drug and user age during the first 7 months of the COVID-19 epidemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 4 publications
(7 reference statements)
3
53
0
Order By: Relevance
“…Other host factors (eg, tolerance to opioids) may temporarily decrease due to pandemic-related barriers that limit acquiring and using opioids, only to be supplanted with an escalation of overdose risk when opioids become more available and used at prehiatus dosage [ 3 , 37 ]. Consistent with this notion, Currie et al [ 38 ] reported an initial fentanyl-fueled spike in opioid overdose deaths in Ohio approximately 6 weeks following the declaration of a national public health emergency on March 13, 2020. Notably, opioid overdose deaths returned to comparable historical levels within approximately 3 months.…”
Section: Discussionmentioning
confidence: 92%
“…Other host factors (eg, tolerance to opioids) may temporarily decrease due to pandemic-related barriers that limit acquiring and using opioids, only to be supplanted with an escalation of overdose risk when opioids become more available and used at prehiatus dosage [ 3 , 37 ]. Consistent with this notion, Currie et al [ 38 ] reported an initial fentanyl-fueled spike in opioid overdose deaths in Ohio approximately 6 weeks following the declaration of a national public health emergency on March 13, 2020. Notably, opioid overdose deaths returned to comparable historical levels within approximately 3 months.…”
Section: Discussionmentioning
confidence: 92%
“…Partygoers in New York City tended to reduce their use of cocaine, ecstasy, and LSD during COVID-related social distancing (Palamar et al, 2021). In contrast, in the state of Ohio, overdose deaths among people aged 24 years and younger in May 2020 were 2.06 times the May 2018-2019 mean (42 vs 20 deaths) (Currie et al, 2021). Most of these overdoses involved opioids, the use of which was not reported in the other publications.…”
Section: Youth Substance Use During Covid-19mentioning
confidence: 82%
“…Reassuringly, there does not appear to be any strong relationship. 16 Mortality and adverse health outcomes generally increase during periods of economic recession and distress (Ruhm 2000); deaths from drug overdoses have increased in the early COVID-19 months (CDC 2020b; Currie et al 2021); and incidence of mental health and suicide ideation are elevated during the pandemic (Czeisler et al 2020).…”
Section: Heterogeneity In Utilization and Mortality At The County And Patient Levelmentioning
confidence: 99%